Reproductive Biology, Morphological Taxonomy, Biogeography and Molecular Phylogeny of Aglaia Lour. (Meliaceae) : The Monographic Approach to a Large Genus of Tropical Trees - Pannell, Caroline M (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
The molecular revolution has given us new opportunities to explore species relationships, evolution and historical biogeography. It is at its most powerful when combined with studies of the living plants in the field and information gleaned from the many thousands of herbarium specimens that go into preparing comprehensive taxonomic revisions. For the genus Aglaia, a genus of more than 100 species, morphological, distributional and biological information has been combined with the history of plate tectonics in the Indo-Malayan Australasian Archipelago, molecular phylogenies and historical biogeographical analyses. Hypotheses for the origin, expansion and species radiation since its origin c. 24 million years ago have been proposed. The tribe Aglaieae was the first monophyletic plant group for which a fully resolved, fossil-dated phylogenetic tree was published. Subsequent studies of some other groups of plants and animals have revealed similar patterns of dispersal, establishment and radiation in the region. The comprehensive nature of the research carried out on this medium-sized genus of tropical rain forest trees has contributed and continues to contribute to an understanding of the Sunda-Sahul floristic interchange and the species radiation that follows dispersal between these continental shelves. The genus is found mainly in lowland tropical rain forests from the Western Ghats of India to Samoa and from southern China to tropical Australia, with its greatest diversity in Malesia. In SE Asia section Aglaia is dispersed by mammals, especially greater and lesser apes (orang-utan, siamang and gibbons). This section of the genus has diversified in New Guinea without its primate dispersers and with no obvious alternative disperser. No marsupial is known to be an efficient seed-disperser. The other two sections of the genus, section Amoora and section Neoaglaia, are bird-dispersed. The coastal and estuarine species, Aglaia cucullata, almost certainly sometimes survives a sea journey. This may partly explain its morphological uniformity over a wide geographical area, from Bangladesh to New Guinea.